Gestão do risco no setor de urgência do hospital público: reconhecimento, saberes e valores na atividade humana dos auxiliares e técnicos de enfermagem - Silvia Dalmázio Fonseca (2019)
ABSTRACT The research presents an investigation about the recognition, knowledge and values of nursing Auxiliaries and Technicians in relation to risk management and the variability of their day-to-day work in the urgency/emergency sector of the public hospital. The proposal was to analyze which articulations are put into motion and how the elements of the order invested in the history of these servers are mobilized, neglected, neglected or even abandoned in the performance of human work activity in the urgency/emergency services sector. Place that presents itself with one of the most critical of the hospital in relation to the quality of care to the user in a warm and resolute way. Emphasizing the vested knowledge of these health servants indicates a differentiated look at the ways in which these professionals manage the actual work activity in an environment often controversial to their own health proposal. In order to discuss the human activity of work, we seek support in the Ergological approach of Yves Schwartz who selects the activity as excellence to perceive, to understand and to transform positively the labor relations. The author presents us the Ergological Epistemology as machining of elements that support us in the understanding of the industrious activity in situation in its entirety, is a reflection that brings together the protagonists of the work situation with the differential of convening multidisciplinary knowledge through plural approaches. Keywords: Ergology; hospital; knowledge; nursing; values; work activity